Design and operation of a microfluidic chip for trapping, and off-chip collection of a few human sperm. (4th June 2018) - Samuel, Raheel; Miller, Nicholas; Badamjav, Odgerel; Jenkins, Timothy; Carrell, Douglas; Hotaling, James; Gale, Bruce K
Abstract: We report a novel sperm trapping microfluidic chip that can trap sperm and then transfer entrapped sperm to individual collectors (cryotips) that can be detached from the chip. We were able to collect sperm in numbers ranging from 3–12 with good recovery of sperm from the cryotip after transfer. Based on our knowledge, this is the first time a microfluidic chip has been designed to enable entrapment of low numbers of cells while provisioning in the design the recovery and subsequent observation of those few cells off the chip. We also discuss the critical design and operational challenges that need to be taken into consideration for the chip to deliver its outcome. The chip has applications in non-invasive analysis and cryopreservation of a few sperm for treatment of severe cases of male infertility.